Progresso no arquivo de projecto: Acesso pelo BIM - Sérgio Rafael de Sousa Vieira (2016)
Among marks on walls and records in mobile support, until today, the collection created by the Architect has been characterized, on one hand, by representative function of building, on the other, by the mark where may be recognized identities associated to times and civilizations on that are created. Even in the twentieth century, with the introduction of the digital in the development of the architect work, it followed functions and maintained nearby relations with the previous paradigm, so that the construction industry has referred the need to improve the methods used so far. The latest tools have evolved in the representation and design, and particularly in the form of communication, taking advantage of sense of progress associated with digital technologies. The BIM seen like a methodology comes from requirements that have arisen in the construction industry and it is presented as a new way to design, keeping the drawing as a basis for communication and adding more references. This methodology makeup itself of BEMs used in project development tools which, for their structure and performance, help to analyze and understand the project, both by the drawing information, as for the written information, may be seen as new elements to be taken into account for the design collection of Architect. Both these elements and others that assist the project development in accordance with this methodology may be organized within a DIM, which can be used to store and manage the information from project stakeholders. Therefore, using as a case study a constructed project - the Portugal Pavilion '98, Álvaro Siza -, it is experimented the creation of a database corresponding to the project, identifying characteristics that are associated with a case of this kind. This is where this dissertation explores this theme: on one hand, the ways to design, manage, and the techniques used by the architect; on the other, by the identify an architecture project database that can support the process of an integrated project using BIM. That said, the data presented allow rethink the composition of the Project File in order to stay more complete and, having been explored a working methodology from the case study for the creation of collections that may be of public interest, in the possibility of disclosure of this information by the Porto School of Architecture, as of the management of its Documentation Center.